HUBUNGAN KONSUMSI VITAMIN D DENGAN KERONTOKAN RAMBUT: LITERATUR REVIEW - Elfi Yulfienti; Abdullah, Dessy; Maryeti Marwazi; Zukhri Zainun (Nusantara Hasana Journal, 2024)
In this study, data were collected from various relevant studies and analyzed in relation to the patterns of vitamin D consumption among subjects experiencing hair loss. Vitamin D plays a crucial role in the process of cell regeneration and the regulation of the hair growth cycle. As a result, a deficiency in this vitamin can contribute to conditions like alopecia. Using a literature review research method, information sources were obtained from academic databases such as PubMed, Google Scholar, and JSTOR. The collected data were analyzed to identify common patterns, study conclusions, and variability in results. This review indicates a significant association between vitamin D deficiency and increased hair loss, as well as the potential benefits of vitamin D supplementation in individuals with this deficiency.